Simulation past, present and future - A decade of progress in simulation-based education in the UK - Higham, H (BMJ Publishing Group, 2020)
This review will present developments in simulation-based education (SBE) over the past decade with a focus on activity in the UK’s National Health Service and the role of the national society (the Association for Simulation Practice in Healthcare). The article covers the evolution of strategic changes for the use of SBE in the UK and the operational challenges faced by clinicians and other faculty in SBE. The expansion of the evidence base to support SBE in healthcare both in technical skills and, more broadly, in interprofessional team training is explored. Finally, the wider role of simulation in patient safety and healthcare systems, including testing pathways and the development of cognitive aids and involvement of patients in SBE is considered.